Implementasi Pendidikan Karakter melalui Pembiasaan di PAUD Sekolah Alam Ungaran - Nur Cahyani; Tri Joko Raharjo (Lifelong Education Journal, 2021)
This study aims to describe the implementation of character education through habituation which includes planning, implementation, evaluation of the results of character education, supporting factors and obstacles to the implementation of character education through habituation in Paud Alam Ungaran. This study uses a qualitative approach with qualitative descriptive methods. Data collection techniques carried out by interview, observation, and documentation. The validity technique uses source and method triangulation. Data analysis techniques in research using data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of character education through the habituation of students in accordance with the stages of planning, implementation, evaluation and results as well as supporting factors and inhibiting factors. Children's character education planning is done through daily habituation in accordance with 9 of the 18 national character values, namely religious, honest, tolerance, discipline, creative, curiosity, friendly / communicative, fond of reading and caring for the environment. Implementation covers the process of implementing character education in daily life through the habituation given by the teacher to children. Evaluation and results are conducted to see the results of changes in children's behavior in accordance with the ethics and morals of character education. The supporting factors of implementing character education through habituation are parents, motivating teachers. The inhibiting factor of the application of character education through habits is from outside the environment and the mindset of children who are still small and do not understand.